Optimal Tax-Subsidy System for an Economy with Marshallian Externalities - Osana, Hiroaki (Econometrica, 1977)
[It is shown that, in a wide class of economies with Marshallian externalities, a Pareto optimum can be sustained by a competitive equilibrium with the aid of a tax-subsidy system. The tax-subsidy system consists of commodity taxes, commodity subsidies, lump-sum taxes, and lump-sum subsidies. The model can be interpreted as describing an economy with various kinds of public goods.]